2006
DOI: 10.1300/j096v11n02_08
|View full text |Cite
|
Sign up to set email alerts
|

Ache, Pain, and Discomfort

Abstract: The main purpose of the study was to investigate the prevalence of perceived symptoms of musculoskeletal disorders (MSD) among workers on large-scale dairy and pig farms in Sweden (herd size more than 300 cows and 450 sows) and to identify potential risk factors in the development of MSD. A study based on questionnaires was carried out among 42 workers on 10 large dairy farms and among 37 workers on 10 large pig farms in Southern Sweden during the autumn of 2002. Most importantly, the study showed that 86% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…In this study, both farmers and workers reported overall high frequencies of work-related MSD and mainly in the lower back, shoulder, neck, knees, and hand/wrists and discomfort from ergonomic work factors such as repetitive and monotonous work. Comparably high frequencies of MSD have also been found in several national and international studies on dairy farmers and workers [4,10,11,18,19,31]. …”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…In this study, both farmers and workers reported overall high frequencies of work-related MSD and mainly in the lower back, shoulder, neck, knees, and hand/wrists and discomfort from ergonomic work factors such as repetitive and monotonous work. Comparably high frequencies of MSD have also been found in several national and international studies on dairy farmers and workers [4,10,11,18,19,31]. …”
Section: Discussionsupporting
confidence: 59%
“…It is well-known that working with dairy farming, milking in particular, is physically demanding, associated with difficult working postures and movements, repetitive and monotonous work tasks, and also associated with injuries caused by slips, trips and falls on slippery floors or barn fittings, which constitutes a risk factor for development of MSD [4,11,18-26]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations